The Role of Shalihah Women in Turning Out Rabbani Generation in The Family Environment - As rori (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study aims to explore how the role of shalihah (pious) women in turning out rabbani generation in a family environment. The study was a qualitative research with library study type by using the method of documentation and observation. The results of this study were concluded: First: There are two characteristics divisions of shalihah women namely: to obey Allah and to obey the husband. Second, the tips in turning out rabbani generation are among: Get used children to do good things, Lead children to the personality of Rasululloh SAW as a role model, Perform Good Exemplary, Pray for the children and Do not curse them, Fill their spare time with useful things, Look for the right time to give instructions, Tell the stories to install the values and virtues for the children. Third, the role of shalihah (pious) women in turning rabbani generation in the family is: women as servants of God, women as mothers and women as role models in their communities. Keywords: Shalihah Women, Rabbani Generation, Family Environment